The Absence of Macpherson and Strauss in Pocock's Machiavellian Moment. Issue 2 (17th February 2017) - Andrew, Edward
SUMMARY: Pocock's Machiavellian Moment is monumental in its erudition, and thus one may be surprised that Pocock virtually ignored Macpherson's Political Theory of Possessive Individualism in his assessment of seventeenth-century political thought, and ignored Strauss's Thoughts on Machiavelli . Pocock noted that 'the schools of Marx, Strauss and Voegelin concur' in holding Locke to be a bourgeois or possessive individualist. Pocock elaborated a paradigm of republicanism as civic humanism as a contrast to liberalism as possessive individualism. Pocock seemed to accept tacitly Macpherson's and Strauss's view that Locke inverted the Aristotelian view of property as a means to political participation, whereby politics became a means to the protection and accumulation of property. Macphersonian scholars have criticised Pocock for misinterpreting the function of property in the Atlantic republican tradition and Straussian scholars have criticised The Machiavellian Moment for its failure to distinguish ancient from modern republics, and for Pocock's failure to appreciate the epochal significance of Machiavelli's call to master fortune or dominate nature through technique. But it is questionable whether or not it is incumbent on an intellectual historian to address present preoccupations about capitalism or global technique.